Analysis of Students' Skills through Practicum on Reaction Rate Topic - Hayatul Islam; Ratman Ratman (Universitas Tadulako, 2021)
National education emphasizes learning on assessing students' knowledge, attitudes, and skills. The development of skills aspect is not enough only relying on the learning in the classroom, but also necessary doing understanding outside the classroom such as practicum in the laboratory. The implementation of training allows students to practice their skills and help students understand the material taught in the class. This study aimed to describe the quality of students' skills on reaction rate topics through a practicum in grade XI at SMA Negeri 5 Palu. This type of research was a quantitative descriptive study with a one-shot case study design. Sampling was conducted by purposive sampling. The sample was Class XI Science 2 as the experimental class 1 with 23 students and Class XI Science 3 as the experimental class 2 with 25 students. The quality skill of students was measured by instruments in the form of observation sheets as the primary data. The data obtained through the observation sheet showed that the average percentage of all aspects of student skills in experimental class 1 was 74.81%, and in experimental class 2 was 74.05%. It indicates that the ten skills elements have emerged in the learning activities with a good category. This study concludes that the quality skill of grade XI students at SMA Negeri 5 Palu on learning reaction rate topic through practicum is a good category.